ADVANTAGES OF INTRODUCING THE DUAL EDUCATION SYSTEM IN TECHNICAL COLLEGES (Web of Teachers: Inderscience Research, 2025)
In this research work, the advantages, problems, and effectiveness of implementing a dual education system in technical schools were analyzed. In the study, foreign and domestic experience was studied, and the theoretical and practical foundations for the development of the dual education system in the conditions of Uzbekistan were developed. From a scientific and methodological point of view, analytical, statistical, survey, and experimental methods were used to study the effectiveness of the system and its impact on the quality of education. The research results showed that dual education plays an important role in enriching the educational process with practical skills, increasing graduate employment rates, and reducing the shortage of qualified personnel in the economy. Existing problems in organizing effective cooperation with manufacturing enterprises, security, and training of qualified personnel were also analyzed. The research results include practical recommendations for the modernization of the education system and the formation of state policy.